Phytotherapy's Impact on Immune Regulation in Degenerative Diseases - Desi Nadya Aulena; Iqbal Julian (Faculty of Pharmacy Universitas Pancasila, 2025)
This literature review looks at how phytotherapy affects immune regulation in degenerative diseases like neurodegenerative, autoimmune, and metabolic disorders. We begin by outlining a theoretical framework that explains how chronic inflammation, caused by pathways such as NF-κB and the NLRP3 inflammasome, plays a central role in these conditions. Next, we explore how different phytochemicals, including flavonoids, stilbenes, and phenolic acids, achieve their therapeutic effects by influencing these important inflammatory pathways, lowering cytokine production, and offering antioxidant support. The review applies this knowledge to specific diseases, emphasizing how compounds like curcumin and resveratrol may help reduce neuroinflammation and improve immune balance. Finally, we discuss the main challenges related to bioavailability and standardization, suggesting future research paths to realize the full potential of these natural compounds as effective strategies for managing chronic degenerative conditions.